2020
DOI: 10.1158/1055-9965.epi-19-1339
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein and Future Risk of Clinical and Molecular Subtypes of Colorectal Cancer

Abstract: Background: Inflammation has been implicated in colorectal cancer (CRC) etiology, but the relationship between C-reactive protein (CRP) and CRC risk is unclear. We aimed to investigate the association between pre-diagnostic plasma CRP concentrations and the risk of clinical and molecular CRC subtypes. Methods: We used prospectively collected samples from 1010 matched CRC case-control pairs from two population-based cohorts in Northern Sweden, including 259 with repeated samples. Conditional logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The positive association with pre-diagnostic CRP was observed for colon but not for rectal cancer, and among men but not women. In the most recent investigation, a populationbased nested case-control study from Northern Sweden, CRP concentrations were not related to subsequent risk of CRC, regardless of CRC location, stage or molecular subtype [9]. In the European Prospective Investigation into Cancer and Nutrition (EPIC), we previously observed that elevated circulating CRP concentrations were associated with a higher risk of colon but not rectal cancer and a higher risk of colon cancer was particularly observed in men but not in women [10].…”
Section: Introductionmentioning
confidence: 94%
“…The positive association with pre-diagnostic CRP was observed for colon but not for rectal cancer, and among men but not women. In the most recent investigation, a populationbased nested case-control study from Northern Sweden, CRP concentrations were not related to subsequent risk of CRC, regardless of CRC location, stage or molecular subtype [9]. In the European Prospective Investigation into Cancer and Nutrition (EPIC), we previously observed that elevated circulating CRP concentrations were associated with a higher risk of colon but not rectal cancer and a higher risk of colon cancer was particularly observed in men but not in women [10].…”
Section: Introductionmentioning
confidence: 94%
“…10 Prognostic scores derived from the combination of several of C-reactive protein (CRP), hsCRP, LYM, and ALB have been constructed and presented better performance than individual indicators. [11][12][13] The high-sensitivity modified Glasgow Prognostic Score (hs-mGPS: the combination of hsCRP and ALB), hsCRP/ALB, and prognostic nutrition index (PNI: the combination of LYM and ALB) have been proposed as predictors for survival of cancer patients. [14][15][16][17][18] A comparative study reported that the prognostic value of Glasgow Prognostic Score (GPS: the combination of CRP and ALB) was better than those of CRP and ALB in patients with hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%